2014
DOI: 10.1177/1358863x14534309
|View full text |Cite|
|
Sign up to set email alerts
|

The role of novel anticoagulants in the management of venous thromboembolism

Abstract: Venous thromboembolism (VTE) is a common health condition with a high mortality and morbidity as well as significant health cost. Traditional treatment with parenteral heparin followed by vitamin K antagonist (VKA) has helped to decrease both morbidity and mortality over years. However, difficulties with warfarin such as INR monitoring, drug-drug interactions, and dietary restrictions has led to research for new anticoagulants. Thus, novel anticoagulants such as direct thrombin and factor X inhibitors have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…So far, a number of sustained release systems for hirudin have been reported in the literature, such as the PEG-hirudin 17 , dextran coupled hirudin 18 , hydrogel based hirudin 19 and cationic liposome delivery system 20 . However, they all suffer from undesired long anticoagulation time that often leads to the increased risk of bleeding, which makes them unsuitable to treat patients 21 . In contrast, peptide S2 exhibited an improved half-life (T 1/2 = 212.2 ± 58.4 min) that is comparable to small molecule drugs such as argatraban 22 and dabigatran (Pradaxa) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…So far, a number of sustained release systems for hirudin have been reported in the literature, such as the PEG-hirudin 17 , dextran coupled hirudin 18 , hydrogel based hirudin 19 and cationic liposome delivery system 20 . However, they all suffer from undesired long anticoagulation time that often leads to the increased risk of bleeding, which makes them unsuitable to treat patients 21 . In contrast, peptide S2 exhibited an improved half-life (T 1/2 = 212.2 ± 58.4 min) that is comparable to small molecule drugs such as argatraban 22 and dabigatran (Pradaxa) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Use of heparin followed by vitamin K antagonists (VKAs) remained unchanged irrespective of the presence of aPL, and LAC may be false-positive due to the anticoagulant treatment. It is now suggested to use rivaroxaban in thrombotic APS [14] and many studies reported that the efficacy and safety had same benefits with traditional anticoagulation therapy [15]. There is no study reporting that Rivaroxaban is a leading factor of the APS, although no antidotes to reverse Rivaroxaban have been reported as well [16].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is initiated in the acute setting and typically continued for at least 6 months following the diagnosis of DVT. Traditional therapy has involved the use of low-molecular-weight heparin bridged to warfarin, but new anticoagulants such as factor Xa (eg, apixaban and rivaroxaban) and direct thrombin inhibitors (eg, dabigatran) are effective for acute and chronic applications (12). The major limitation of anticoagulation as an isolated therapy for acute DVT is its lack of a thrombolytic effect, which limits the speed and extent of venous recanalization for large clots and, in turn, leads to prolongation of acute symptoms, more severe venous valvular damage,…”
Section: Treatment Modalities Systemic Anticoagulationmentioning
confidence: 99%